Recognition and enforcement of the awards of the International Arbitral Tribunal at the Belarusian Chamber of Commerce and Industry pursuant to the New York convention of 1958: the case of Austria - Schirinsky, Oleg Yu. (Journal of the Belarusian State University. International Relations, 2020)
The standards of enforcement of arbitral awards arising from the New York сonvention of 1958 are examined, drawing on the example of Austria. Specifically, we review the process of enforcing awards of the International Arbitral Tribunal under the Belarusian Chamber of Commerce and Industry by an Austrian court of first instance. The aim was to develop a protocol of action for Belarusian lawyers to secure recognition and enforcement in Austria of awards of the International Arbitral Tribunal under the Belarusian Chamber of Commerce and Industry. We provide recommendations grounded in the results of our study.